Inactivation of DNA Mismatch Repair by Increased Expression of Yeast MLH1 - Shcherbakova, Polina V. (American Society for Microbiology, 2001)
Inactivation of DNA mismatch repair by mutation or by transcriptional silencing of the MLH1 gene results in genome instability and cancer predisposition. We recently found (P. V. Shcherbakova and T. A. Kunkel, Mol. Cell. Biol. 19:3177–3183, 1999) that an elevated spontaneous mutation rate can also result from increased expression of yeast MLH1. Here we investigate the mechanism of this mutator effect. Hybridization of poly(A)(+) mRNA to DNA microarrays containing 96.4% of yeast open reading frames revealed that MLH1 overexpression did not induce changes in expression of other genes involved in DNA replication or repair. MLH1 overexpression strongly enhanced spontaneous mutagenesis in yeast strains with defects in the 3′→5′ exonuclease activity of replicative DNA polymerases δ and ɛ but did not enhance the mutation rate in strains with deletions of MSH2, MLH1, or PMS1. This suggests that overexpression of MLH1 inactivates mismatch repair of replication errors. Overexpression of the PMS1 gene alone caused a moderate increase in the mutation rate and strongly suppressed the mutator effect caused by MLH1 overexpression. The mutator effect was also reduced by a missense mutation in the MLH1 gene that disrupted Mlh1p-Pms1p interaction. Analytical ultracentrifugation experiments showed that purified Mlh1p forms a homodimer in solution, albeit with a K(d) of 3.14 μM, 36-fold higher than that for Mlh1p-Pms1p heterodimerization. These observations suggest that the mismatch repair defect in cells overexpressing MLH1 results from an imbalance in the levels of Mlh1p and Pms1p and that this imbalance might lead to formation of nonfunctional mismatch repair complexes containing Mlh1p homodimers.